WADY WRODZONEIntratissular biodegradable annuloplasty rings. Application in paediatric cardiac surgery - Mrówczyński, Wojciech; Mroziński, Bartłomiej; Pawelec-Wojtalik, Małgorzata; Kalangos, Afksendyios; Wojtalik, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Aim: To assess safety and outcome of implantation of intratissular biodegradable annuloplasty rings in children with regurgitant atrioventricular valves. Material and Methods: In the period between 2005 and 2008 38 patients were operated on for severe insufficiency of atrioventricular valves (24 – TI, 12 – MI, 2 – TI+MI). Reconstruction of the valve was followed by implantation of a biodegradable ring. All patients were prospectively followed up by transthoracic echocardiography. Results: Median ECC time was 100 min for patients with TI and 91.5 min for children with MI. Two early deaths were observed in patients with Ebstein’s anomaly due to postoperative low cardiac output syndrome. No late deaths occurred. Median follow-up time was 747 days (171-1405) in the TI group (100% frequency) and 389.5 days (41-1113) in the MI group (92.9% frequency). Median TI fraction decreased significantly from 39% (10-93) to 11% (0-29) at discharge (p < 0.001) and was 10% (0-30) at the last examination (p < 0.001). Age at operation did not significantly influence the outcome. Median MI fraction decreased significantly from 38% (22-69) to 12% (0-31%) at discharge (p = 0.0002) and equalled 14% (0-46%) at the end of follow-up (p = 0.006). Younger patients had significantly higher postoperative insufficiency fractions. Due to increase of insufficiency fractions 2 patients required mitral valve replacement after an unsuccessful re-repair. Conclusions: The implantation of biodegradable rings is safe and enables uncomplicated native annulus reinforcement. Early and short-term results are satisfactory. However, outcomes of younger patients with complex MI are worse.